2012
DOI: 10.1073/pnas.1121003109
|View full text |Cite
|
Sign up to set email alerts
|

Direct conversion of mouse fibroblasts to self-renewing, tripotent neural precursor cells

Abstract: We recently showed that defined sets of transcription factors are sufficient to convert mouse and human fibroblasts directly into cells resembling functional neurons, referred to as "induced neuronal" (iN) cells. For some applications however, it would be desirable to convert fibroblasts into proliferative neural precursor cells (NPCs) instead of neurons. We hypothesized that NPC-like cells may be induced using the same principal approach used for generating iN cells. Toward this goal, we infected mouse embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
357
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(370 citation statements)
references
References 34 publications
11
357
0
2
Order By: Relevance
“…Later, the same strategy was successfully applied to mouse tail tip fibroblasts and generated iNSCs with neurogenesis potency both in vitro and in vivo, which further confirmed the feasibility of this method [6]. Meanwhile, Wernig and colleagues also reported a similar screening of 11 factors using a Sox2-EGFP reporter MEF system, and found that as few as two factors, FoxG1 and Sox2, were able to generate selfrenewing, bipotent iNSCs [3]. When Brn2 was added to the combination, tripotent iNSCs, which gave rise to functional neurons, astrocytes as well as oligodendrocytes, were obtained [3].…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Later, the same strategy was successfully applied to mouse tail tip fibroblasts and generated iNSCs with neurogenesis potency both in vitro and in vivo, which further confirmed the feasibility of this method [6]. Meanwhile, Wernig and colleagues also reported a similar screening of 11 factors using a Sox2-EGFP reporter MEF system, and found that as few as two factors, FoxG1 and Sox2, were able to generate selfrenewing, bipotent iNSCs [3]. When Brn2 was added to the combination, tripotent iNSCs, which gave rise to functional neurons, astrocytes as well as oligodendrocytes, were obtained [3].…”
mentioning
confidence: 54%
“…However, the innate limitations of iNs may restrict their applications in the clinic. Very recent publications describe the direct conversion of mouse somatic cells into induced neural stem cells (iNSCs) [1][2][3][4][5][6]. Together with other reports [7,8], they constitute the basis for a rising concept that priming and retaining reprogrammed cells into an expandable neural progenitor stage may render them to be more amenable and with great potential for both disease modeling and possible therapeutic treatment for neurological diseases.…”
mentioning
confidence: 99%
“…Transdifferentiation from other type of somatic cells into functional neurons has allowed the generation of mature neurons in a relatively shorter period, which seems to be an ideal source of cells for transplantation, nevertheless, the efficiency of transdifferentiation is low, and the iNs are not expandable for large quantity. Alternative procedures that convert other type of somatic cells into expandable neural stem cells are also under extensive exploration (Kim et al, 2011;Han et al, 2012;Lujan et al, 2012;Ring et al, 2012;Sheng et al, 2012;Thier et al, 2012). In contrast to the iNs, the induced neural stem cells (iNSCs) are capable to proliferate, thus allow yield of larger quantity of cells through selectively amplification of the induced neural stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Lujan et al recently reported the generation of self-renewing induced neural precursor (iNP) cells from mouse embryonic fibroblasts using five factors (Rfx4, ID4, FoxG1, Lhx2, and Sox2) (Lujan et al, 2012). The transfection of these factors into mouse embryonic fibroblasts (MEFs) was sufficient to induce Sox2-EGFP+ colonies, as assessed 24 d after infection.…”
Section: Direct Reprogramming Of Non-neural Cells To Neural Stem Cellsmentioning
confidence: 99%